Paradigma Evaluasi Pembelajaran di Era Society 5.0 /Abad Ke-21 - Nofrianti Enliyani Tualaka; Vivi Elviana Nuban; Keti Regina Runesi (Indo Publishing, 2026)
The rapid advancement of digital technology in the Society 5.0 era has driven significant transformations in various aspects of education, including learning evaluation. Evaluation is no longer viewed merely as a tool for measuring learning outcomes but also as a process aimed at developing students’ competencies, character, and skills holistically. This study aims to analyze the paradigm shift in learning evaluation relevant to the demands of 21st-century education and to examine the integration of digital technology and Artificial Intelligence (AI) in modern evaluation systems. The study employed a qualitative approach using a literature review method by examining various scientific sources, including books, journal articles, and educational policy documents. The findings indicate that learning evaluation in the Society 5.0 era has shifted from an outcome-oriented approach to a process-oriented evaluation that emphasizes competency development and character building. Modern evaluation is characterized by authentic assessment, digital technology integration, AI utilization, and the measurement of Higher Order Thinking Skills (HOTS). As a conceptual contribution, this study proposes the Human-Centered Digital Evaluation model, which integrates AI-Based Assessment, HOTS Evaluation, Character Assessment, Continuous Feedback, and Personalized Learning Evaluation as an adaptive and human-centered evaluation framework. However, the implementation of this paradigm still faces challenges, including limited infrastructure, disparities in digital literacy, and ethical concerns regarding technology use. Therefore, strengthening teacher competencies, providing adaptive policy support, and improving technological infrastructure are necessary to establish an effective and future-oriented learning evaluation system.